siRNA Targeting and Treatment of Gastrointestinal Diseases - Rachel Chevalier (Wiley, 2019)
RNA interference via small interfering RNA (siRNA) offers opportunities to precisely target genes that contribute to gastrointestinal (GI) pathologies, such as inflammatory bowel disease, celiac, and esophageal scarring. Delivering the siRNA to the GI tract proves challenging as the harsh environment of the intestines degrades the siRNA before it can reach its target or blocks its entry into its site of action in the cytoplasm. Additionally, the GI tract is large and disease is often localized to a specific site. This review discusses polymer and lipid‐based delivery systems for protection and targeting of siRNA therapies to the GI tract to treat local disease.